L'interés de Gaspar Escolano per la llengua i la literatura medievals i per Ramon Llull, a la Década primera de la historia de Valencia (1610). - HERÈDIA, LAURA ROMÀ (Scripta)
This work is an approach to a classic of historiography of València in the XVII century, Década primera de la insigne i coronada ciudad i reyno de Valencia (València 1610), of Gaspar Escolano, looking in the interest of the chronicler in Catalan medieval authors. Especially in Jaume I --like a founder of the Regne de València-- and also in Jordi de Sant Jordi, Andreu Febrer, Jaume Roig and Ramon Llull to which devotes several chapters.